Germ line imprinting in Drosophila: Epigenetics in search of function - Menon, Debashish U.; Meller, Victoria (Fly (Austin, Tex.), 2010)
Germ line imprinting produces parent-specific differences in the behavior of chromosomes or expression of genes. Epigenetic marks, placed on chromosomes in the parental germ line, govern classical imprinted effects such as chromosomal inactivation, chromosome elimination and mono-allelic expression. Germ line imprinting occurs in insects, plants and mammals. Several Drosophila systems display imprinted effects. In spite of this, many aspects of imprinting in flies, including the normal function of this process, remain mysterious. Transgenerational inheritance of epigenetic marks is a powerful force in genome regulation. Elucidation of the mechanism of imprint establishment and maintenance in a model organism, such as Drosophila, is thus of great interest. In this review we summarize the primary systems that have been used to study imprinting in flies and speculate on the origin and biological function of imprinting in Drosophila.